Automatic lighting system (ALS) for Taman Tas Eco Shop by using Arduino Uno - Norfadilah, Harjo (2019)
Nowadays, many sophisticated devices have been implemented in our lives in many kinds of places for a living. The importance of this kind of devices is to ease human daily life activities and improve the performance of products. Not being left behind, a technology for automatic lighting switching system is created and has been used in building likes home especially. It is used to control and monitor devices and hardware in house to deliver some functions. However, this kind of system for ECO Shop store is unusual found yet. A project named as Automatic Lighting System (ALS) is designed for Taman Tas ECO Shop store branch that selling daily things at price RM2.10 for each. Currently, Taman Tas ECO Shop branch is using manual lamp switching control which is the management assigns Supervisor Assistant only as person-in-charge to turn on or off the lamps every day. However, this store only has two person-in-charge so both of them cannot leave the store at the same time even in any situation. Therefore, it will be problem if that person-in-charge comes late before operating hours so the other workers cannot do their job earlier than operating hours. Besides that, extra electricity consumption also can happen if person-in-charge forgot to switch off lamps after operating hours. So, Taman Tas ECO Shop store branch need enhancement in controlling the lamps utilization before and after operating hours. By using ALS project, client can make the duty of lighting switching become easier and well-controlled. The project is divided into two main components which is a system that installed in computer to control Arduino Uno, and the second component is hardware includes Arduino Uno, sensor and other extra hardware. In conclusion, hope this project can bring benefits and fulfil client requirements.